2012
DOI: 10.1084/jem.20112258
|View full text |Cite|
|
Sign up to set email alerts
|

Epidermal ADAM17 maintains the skin barrier by regulating EGFR ligand–dependent terminal keratinocyte differentiation

Abstract: EGFR requires ADAM17 activity to preserve skin barrier homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(107 citation statements)
references
References 69 publications
3
104
0
Order By: Relevance
“…Moreover it delays apoptosis during early differentiation in suprabasal keratinocytes that have lost their interaction with the matrix89. However, EGFR-ligands are also abundant in differentiated epidermis and there are several evidences that EGFR signalling contributes to terminal keratinocyte differentiation and skin barrier formation10111213. EGFR deficiency causes defects in hair follicle development and immature epidermal differentiation with inflammatory skin reactions in both mice and humans14151617.…”
mentioning
confidence: 99%
“…Moreover it delays apoptosis during early differentiation in suprabasal keratinocytes that have lost their interaction with the matrix89. However, EGFR-ligands are also abundant in differentiated epidermis and there are several evidences that EGFR signalling contributes to terminal keratinocyte differentiation and skin barrier formation10111213. EGFR deficiency causes defects in hair follicle development and immature epidermal differentiation with inflammatory skin reactions in both mice and humans14151617.…”
mentioning
confidence: 99%
“…IEC proliferation is critical for adaptive growth after intestinal injury/inflammation (47,48), and EGFR/ErbB is a major mediator of these IEC responses (44,48,49). In the DSS colitis model, hypomorphic Egfr mice and ErbB ligand-deficient mice display exacerbated intestinal inflammation (50,51), whereas more recent studies using different IEC-ErbB KO mice have shown that all four ErbB receptors contribute, in various degrees, to protection against DSS-induced colitis (19,24,26,45). Evidence that ADAM17 is an upstream regulator of EGFR/ErbB signaling in the DSS colitis model comes from analysis of hypomorphic Adam17 mice under continuous exposure to low-dose DSS (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of ADAM17 to regulate ectodomain processing of additional substrates was clearly demonstrated by the fact that Tace ⌬Zn/⌬Zn mice display perinatal lethality, whereas TNF-␣-deficient mice or mice lacking TNFRs are viable and fertile (11,12). The developmental defects observed in Tace ⌬Zn/⌬Zn mice are characteristic of EGFR-deficient (Egfr Ϫ/Ϫ ) mice (14,15), and the defects in skin, heart valve, and mammary gland development have been directly attributed to the inability to process and activate specific EGFR ligands (16)(17)(18)(19).…”
Section: Micementioning
confidence: 99%
“…The classical skin tumor promoter, TPA, has been shown to induce skin tumorigenesis via activation of various inflammatory pathways. A recent study demonstrated that mice overexpressing TACE shows augmented dermal fibrosis and inflammation in response to TPA 25 , however, mice lacking TACE in keratinocytes develops spontaneous dermal inflammation 26,27 . The present study was designed to demonstrate the effect of a selective TACE inhibitor on skin inflammation and tumorigenesis induced by TPA in mice.…”
Section: Discussionmentioning
confidence: 99%